Pengaruh Lingkungan Kerja, Stress Kerja, Dan Komunikasi Interpersonal Terhadap Kinerja Guru Di SMKN 3 Kediri - Yuriska Gangsar Wati; Anita Sumelvia Dewi; Agung Pambudi Mahaputra (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
Human Resource Management (HR) is recognized as an important global issue in the competitive arena in the era of globalization. It is undeniable that many problems that arise in the development and competition of companies are human-rooted By taking a sample of 72 teachers at SMKN 3 Kediri using correlation and regression analysis techniques. The results of the analysis concluded: 1) The work environment has a negative and significant effect on teacher performance at SMKN 3 Kediri. 2) Work stress does not have a positive and significant effect on teacher performance at SMKN 3 Kediri. 3) Interpersonal communication has a positive and significant effect on teacher performance at SMKN 3 Kediri. 4) Simultaneously it is known that there is a significant influence between work environment, work stress, and interpersonal communication on teacher performance at SMKN 3 kediri.